The female Saudi poets and their role in the literary renewal - Zamri Ariffin; Mariam Mat Daud (Universiti Kebangsaan Malaysia, 2013)
Women have become one of the fundamental pillars of the construction and progress of society and civilization where they are able to participate in the public opinion in respect to communal issues. Their personality transcends the history, the more they are given attention and care in the community, the more they become innovative and show their effective role in the construction of human civilization, as well as showing their contributions in cultural and literary movement, resulted from their significant role in drawing the life of community and prosperity of civilization. Here the Saudi women poets embodied with talents and creativity leave a clear mark on the literary scene, their self-expression, their community and humanitarian crisis. This article contains some features of literary creativity of the Saudi women poets, and the extent of their impact on the literary scene. This study is made possible through reading and examining the most important works known as “the feminist poem” produced by educated women. The article discusses the poetry of some contemporary women and the environment that make them distinctive social class that influences the course of life.